Think a compelling introduction to philosophy - Blackburn, Simon 1944- (Oxford Univ. Press, 1999)
"Simon Blackburn begins by putting forward a convincing case for the study of philosophy and goes on to give the reader a sense of how the great historical figures such as Descartes, Hume, Kant, and Wittgenstein have approached its central themes."